2014
DOI: 10.1245/s10434-014-3752-0
|View full text |Cite
|
Sign up to set email alerts
|

The Extent of Extracapsular Extension May Influence the Need for Axillary Lymph Node Dissection in Patients with T1–T2 Breast Cancer

Abstract: Background Whether extracapsular extension of tumor (ECE) in the sentinel lymph node (SLN) is an indication for axillary dissection (ALND) in patients managed by ACOSOG Z0011 criteria is controversial. Here we examine the correlation between ECE in the SLN and disease burden in the axilla. Methods Patients meeting Z0011 clinicopathologic criteria (pT1-T2,cN0 with <3 positive SLNs) were selected from a prospectively maintained database (2006-2013). Chart review documented presence/extent of ECE. Neoadjuvant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 26 publications
5
55
0
5
Order By: Relevance
“…ACOSOG Z0011 did not define a volume of microscopic extracapsular extension that mandated ALND, and this is often left to surgeon judgment. One study reported that >2mm of extracapsular extension was associated with a heavy nodal disease burden 33 ; however, need for ALND because of extracapsular extension remains an ongoing area of debate. Even with these limitations, we feel that the findings in this study will aid in counseling patients interested in optimizing avoidance of ALND.…”
Section: Discussionmentioning
confidence: 99%
“…ACOSOG Z0011 did not define a volume of microscopic extracapsular extension that mandated ALND, and this is often left to surgeon judgment. One study reported that >2mm of extracapsular extension was associated with a heavy nodal disease burden 33 ; however, need for ALND because of extracapsular extension remains an ongoing area of debate. Even with these limitations, we feel that the findings in this study will aid in counseling patients interested in optimizing avoidance of ALND.…”
Section: Discussionmentioning
confidence: 99%
“…79 Studies have shown that focal ECE is present in the SLNs of 19% to 30% of cN0 patients with early-stage breast carcinoma. 8083 To date, the significance of microscopic ECE in SLNs in the selection of patients for ALND or axillary radiotherapy has not been thoroughly assessed. ACOSOG Z0011 excluded patients with matted nodes and gross ECE but had no specific policy regarding microscopic ECE.…”
Section: Questioning the Benefit Of Completion Alnd In All Sln-positimentioning
confidence: 99%
“…If post-mastectomy radiotherapy including the regional nodes is indicated according to local protocols due to the positive SLN per se, ALND can be safely omitted, a lesson learned from EORTC AMAROS [12,31.] Finally, potential predictors of high nodal disease volume are sometimes used in clinical practice to indicate ALND; the most common are lymph node metastases detected by imaging before surgery and microscopic extranodal disease in the SLN [32,33,34] While the extent of extracapsular extension may influence the need for ALND [35], a positive imaging-guided axillary lymph node needle biopsy does not accurately predict the need for ALND [23.] BOOG 2013-07 from the Netherlands, SERC/IPC 2012-001 from France and the Alliance trial A011202 may eliminate most of the remaining indications for ALND, potentially leaving only confirmed palpable lymph node metastases as the last absolute indication for ALND in the near future.…”
Section: Current and Future Axillary Treatmentmentioning
confidence: 99%